Autoimmune Diseases: An Introduction - Shakya, Shubha Ratna (Nepalese Journal of Zoology, 2015)
The immune system recognizes and eliminates foreign agents, and protects the host against infection. Autoimmunity is a natural phenomenon where self-reactive antibodies and autoimmune cells are present in all individuals. A combination of genetic predisposition and environmental factors contribute to the development of autoimmune diseases. Autoantibodies attack structures within individuals that produce them. Autoimmunity is a major cause for a number of serious and fatal diseases. Presence of one autoimmune disease increases the chance for simultaneously developing other autoimmune diseases in the same person.